2001
DOI: 10.1029/2001wr000491
|View full text |Cite
|
Sign up to set email alerts
|

Travel times of nonlocal dispersion and their geoelectric approximation in Nevada's fractured welded tuffs

Abstract: Abstract. This technical note argues the importance of incorporating nonlocal dispersion effects when modeling contaminant travel times. Using the transport theory of Di Federico and Neuman [1998], expressions for nonlocal contaminant travel times and breakthrough are developed. They show that nonlocal travel times are significantly faster than their local (Fickian) counterpart and that nonlocal breakthrough occurs significantly earlier than All= C1F(1 + 2H) sin (•rH) F(-2H) I + 2H (•t)•+2H'where the right-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Both spectra are power‐law structured and of identical log‐log slope, indicating eh flow patterns of a common fractal dimension. Purvance [2001] observed that this fractal dimension is the same as the fractal dimension of fracture lengths measured in the same formation at Yucca Mountain, Nevada, located in Figure 1.…”
Section: Apparent Resistivity Spectral Analysissupporting
confidence: 76%
“…Both spectra are power‐law structured and of identical log‐log slope, indicating eh flow patterns of a common fractal dimension. Purvance [2001] observed that this fractal dimension is the same as the fractal dimension of fracture lengths measured in the same formation at Yucca Mountain, Nevada, located in Figure 1.…”
Section: Apparent Resistivity Spectral Analysissupporting
confidence: 76%
“…Using standard methods of stochastic analysis, the truncated mode superposition approach allows one to investigate flow [ Di Federico and Neuman , 1998a] and transport [ Neuman , 1990, 1995; Di Federico and Neuman , 1998b; Purvance , 2001] in a hydraulic conductivity field with evolving scales of spatial variability. It allows one to upscale and downscale the random equivalent mean hydraulic conductivity of a domain embedded within such a field and assess its variance and spatial autocorrelation function, conditioned on a known mean value of support‐scale conductivity across the domain [ Di Federico et al , 1999; Hyun et al , 2002].…”
Section: Introductionmentioning
confidence: 99%